Assessment of carbon dioxide exchange processes between water bodies and the atmosphere - P.S. Korotkih; E.N. Neverov; I.A. Korotkiy (Caspian Journal of Environmental Sciences)
Calculating the volume of carbon dioxide absorbed by the ocean is a challenging task because it depends on numerous factors, including depth, temperature, salinity, and others. Calculating the precise volume of CO2 absorbed by the ocean is even more difficult due to the complex and dynamic nature of these processes. Some studies and models provide only an approximate assessment of the annual carbon balance between the atmosphere and the ocean. The purpose of the present study was to examine the processes of CO2 exchange between water and the surrounding environment. For experimental testing, the authors developed a special apparatus used to conduct a series of studies to assess CO2 exchange processes between water and the environment. Studies were performed on distilled, fresh, and salt water. Dissolving CO2 in fresh and salt water is a complex process that plays a key part in the environment's biological, climatic, and geochemical aspects. The initial CO2 concentration in the operational volume of the experimental setup was 5,000 ppm (parts per million; 5%). The temperature inside the chamber amounted to 20 ± 2 ºC. The experiment lasted 10 days. Since the most important factor in the experiment was precision, the study employed the method of gas chromatography. Investigation of these features provided a better understanding of the importance of managing CO2 levels and its impact on Earth’s ecosystem.